Paavo Kallio (1914-1992) - Koponen, Seppo; Hurme, Heli (ARCTIC, 1992)
Professor Paavo Kallio died on 11 June 1992 in Turku, Finland. He was a botanist, a scholar on subarctic and arctic nature, and an enthusiastic supporter of international research in northern areas. . In the mid-1950s he organized field excursions for students to Lapland, and as a result of these trips a site for a field station was chosen in the northernmost part of Finnish Lapland at Kevo in Utsjoki (69 45 N). Even after retiring from his professorship, Paavo Kallio, the founder and the long-term head (1956-76) of the Kevo Subarctic Research Institute of the University of Turku, continued to serve as chairman of the board at Kevo (1977-84). . Professor Kallio also founded three forest-line arboreta at Kevo, where tree-line trees from different parts of the Holarctic region have been planted. . Kallio's aim was to make Kevo (and the biogeographical province Inari Lapland, 23 000 km² in area) into a 'known point," a well-studied reference site for subarctic Fennoscandia. . He also supported research on the two most important animals in the native Sami people's daily life, reindeer and salmon. Kallio was an activist in the founding of the Sami Museum in Inari and acted as an expert in the planning of the Arctic Center in Rovaniemi. In addition to his scientific papers, he published numerous popular articles and books on nature and biological research in the northern Holarctic region. .